NOVEL TARGETS AND THERAPIES IN MULTIPLE MYELOMA - Meral Uluköylü Mengüç (Hematology, Transfusion and Cell Therapy)
Multiple Myeloma (MM) is the second most frequent cancer and constitutes 10 % of hematological malignancies. Median age at onset is older than 65 years old.Despite significant improvement has been gained for management of the diasease in the last decades cure has not been achieved. Clinicial use of monoclonal antibodies targeting cluster of differentiation (CD) 38 or signaling lymphocye activation molecular family 7 (SLAMF7) combined with immunomodulatory drugs and preoteosome inhibitors lead to prolonged progression free survival in a group of relapsed refractory MM (RR MM) patients.High risk disease forms such as extramedullary involvement, advanced stage or poor cytogenetic features still suffer decreased survival. Novel immunotherapies targeting B cell maturation antigen (BCMA), G protein- coupled receptor family C group 5 member D (GPRC5D), Fc receptor homolog 5 (FcRH5), CD138, CD 48, CD 56 and CD74 as well as cellular therapies such as chimeric antigen receptor (CAR) T / CAR NK cells therapies has been emerging.Daratumumab, elotuzumab and isotuxumab are approved monoclonal antibodies that have been in clinical use since 2015. Thereafter Belantamab mafodotin,AMG 224 and MEDI 2228 are the examples of antibody- drug conjugates with the approval of Belantamab after 4 lines of therapy in relapsed refractory MM.Teclistamab and elranatamab are the approved bispesific antibodies targeting BCMA on MM cells and CD3 on T lymphocytes. They both showed overall response rate exceeding 60 % in RRMM. Cytokin release syndrome was observed in two thirds of patients but were mostly low grade. Bispesifics showed objective responses on patients with prior antiBCMA targeted and CAR-T directed therapies.Two CAR T cell therapies has been approved in MM up to date. Idecabtagene vicleucel (ide-cel) and ciltacabtagene autocel (cilta-cel) are anti BCMA autologous CAR T cell products that have FDA approvals in RRMM.Both agents improved progression free survival compared to standard regimens. Allogeneic anti BCMA CAR T cells can also be an option in a near future based on earlier phase trials.Along with approved novel agents investigational studies for earlier lines of therapy and newer agents are emerging.Minimal residual disease (MRD) negativity is an emerging term for depth of response giving the possibility of cure and novel agents promise better MRD negativity as well as disease control.